Peningkatan Kualitas Timbang Terima Di Instalasi Gawat Darurat Era Revolusi Industri 4.0 - Tri Andri Pujiyanti; Luky Dwiantoro; Muhammad Hasib Ardani (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2019)
A handover is an application form for improving effective communication which is part of the patient safety goal. Ineffective handover has been shown to increase the risk of preventable side effects, length of stay and rates of complications. High patient mobilization, a lot of time taken, and increased workload are reasons why nurses do not have time for handover. While the ER Nurses are also required to develop, improve their knowledge and skills to improve quality services in line with the technological development of the era industrial revolution 4.0. The objective of this review to identify efforts for improving quality of handover in Emergency Departement in accordance with the development of the industrial revolution era 4.0. This review source search through CINAHL Ebsco, Science Direct, and pubmed from 2010 to 2019, in English, and full text. Searching keywords are Improvemenr, Quality Handover, Technology, and Emergency Department. From this literature review, it was found that efforts to improve quality of handover in the emergency departement included the establishment of appropriate communication / protocol tools / frameworks, developing multi-disciplinary teams, recognizing the influence of culture and implementing training. These efforts cannot be separated, all are interrelated to realize quality handover. Facing the digital revolution 4.0 based on Cyber Physical Systems in the health sector, improving quality handover may use electronic communication framework. Materials handover is using patient data in the medical record (RM) or electronic medical record (ERM). Electronic Handover tool aswer the challenges for facing the digital revolution 4.0. Efforts to improve the quality of handover in the emergency department are established effective communication tools / frameworks, Multidicipline Team meetings, training / coaching and recognizing cultural influences.